A COMPREHENSIVE FRAMEWORK FOR ASSESSING TRANSLATION ACCURACY (Journal of Foreign Language Studies, 2025)
Accuracy is a fundamental element in translation research and practice, but a comprehensive theoretical framework for the analysis and assessment of this element is lacking. This study proposes a theoretical framework that systematically delineates the key components of accuracy in translation. Through an examination of existing theories, the proposed framework consists of three fundamental components: (1) equivalent meaning; (2) text organisation; and (3) grammatical structure. The theoretical framework not only aims to enhance the efficacy of translation teaching and research but also provides support for translation organisations in evaluating translation quality. However, the study has limitations, including the lack of empirical data to validate the framework’s reliability and its limited applicability to certain text types, language pairs, and user expertise levels. Future research should focus on large-scale validation and the development of evaluation metrics for practical application.
Keywords: Translation; translation accuracy; translation framework